2020
DOI: 10.3389/fpubh.2020.555013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Pathogen Using Family-Wide PCR: Initial Confirmation of COVID-19 in Thailand

Abstract: In resource-limited countries, early detection of novel pathogens is often challenging, due to financial and technical constraints. This study reports the efficacy of family-wide polymerase chain reaction (PCR) in screening, detecting, and identifying initial cases of the novel SARS-CoV-2 in Thailand. Respiratory secretions were collected from suspected individuals traveling from Wuhan, China to Thailand at the beginning of January 2020. Family-wide PCR assays yielded positive results for coronavirus in one tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…At a low copy number of SARS-CoV-2 (Ct > 30) in wastewater specimens, the X-CoV PCR showed a higher sensitivity than the Q-CoV PCR assay (Table S3), which is hypothesized to be due to the number of primer mismatches. The W-CoV PCR could not detect SARS-CoV-2 in clinical samples and laboratory strains due to eight primer mismatches within the reverse primers [19,25], as confirmed in our study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…At a low copy number of SARS-CoV-2 (Ct > 30) in wastewater specimens, the X-CoV PCR showed a higher sensitivity than the Q-CoV PCR assay (Table S3), which is hypothesized to be due to the number of primer mismatches. The W-CoV PCR could not detect SARS-CoV-2 in clinical samples and laboratory strains due to eight primer mismatches within the reverse primers [19,25], as confirmed in our study.…”
Section: Discussionsupporting
confidence: 80%
“…The Q-CoV PCR primers were designed in 2010 to detect bat SARS-like CoV using degenerate primers [ 26 ]. Despite 2–4 primer mismatches to SARS-CoV-2 ( Table S6 ), this protocol successfully detected the first COVID-19 case in Thailand [ 25 ], while the X-CoV PCR primers were newly designed in 2020 and have a 0–1 primer mismatch to SARS-CoV-2. Both assays have equal sensitivity at PCR Ct values less than 31 in human specimens ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanding this comparison to four other studies that identified earlier cases, we inferred January 7, 2020 (95% CI December 22, 2019) as the most likely first case in Thailand. This is only 1 day after a case identified in a traveller to Thailand from Wuhan on January 8, 2020 [ 15 , 16 ]. However, the most likely first case in France was inferred as January 19, 2020 (95% CI January 4, 2020), while a retrospective review of medical records identified one patient as having COVID-19 from December 27 [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, HTS demonstrates superior sensitivity and speci city, enabling the identi cation of low-concentration pathogen nucleic acids and even offering effective detection for rare pathogens [11]. Additionally, this technology can uncover novel, previously unidenti ed pathogens [12]. By comparing and analyzing unknown sequences, it provides fresh insights for disease diagnosis and etiological research.…”
Section: Discussionmentioning
confidence: 99%